Urinary exosomes-based Engineered Nanovectors for Homologously Targeted Chemo-Chemodynamic Prostate Cancer Therapy via abrogating EGFR/AKT/NF-kB/IkB signaling. (August 2021) - Pan, Shaojun; Zhang, Yuhui; Huang, Mark; Deng, Zhoufeng; Zhang, Amin; Pei, Lijia; Wang, Lirui; Zhao, Weiyong; Ma, Lijun; Zhang, Qian; Cui, Daxiang
Abstracts: Multi-functional nanovectors based on exosomes from cancer cell culture supernatants in vitro has been successfully utilized for tumor-specific targeting and immune escape. However, the labor-intensive purification procedures for rich-dose and high-purity homogeneous exosomes without using targeting ligands are still a challenging task. Herein, we developed a nanovector Exo-PMA/Fe-HSA@DOX through cloaked by urinary exosome membrane as a chemo/chemodynamic theranostic nano-platform for targeted homologous prostate cancer therapy which pertain to the abrogation of Epidermal Growth Factor Receptor (EGFR) and its downstream AKT/NF-kB/IkB signaling instead of ERK signaling cascades. Urinary exosomes-based nanovectors own the same urological cancer cell membrane antigen inclusive of E-cadherin, CD 47 and are free from intracellular substance such as Histone 3 and COX Ⅳ. The targeting properties of the homologous cancer cell are well preserved in Exo-PMA/Fe-HSA@DOX nanovectors in high purity. Meanwhile, the nanovectors based on urinary exosomes from prostate patients deeply penetrated into prostate cancer DU145 3D MCTS, and successfully achieve superior synergistic low-dose chemo/chemodynamic performance in vivo . In addition, the blockage of bypassing EGFR/AKT/NF-kB/IkB signaling pathway is greatly enhanced via elevated intracellular PMA/Fe-HSA@DOX nanoparticles (NPs). It is expected that the rich source and high purity of urinary exosomes offer a reliable solution for mass production of such nanovectors in the future. The targeted homologous cancer therapy based on the urinary exosomes from cancer patients exemplifies a novel targeted anticancer scheme with efficient and facile method.